Learning from Failures of Co-owned Firms: Common Ownership and Information Disclosure Fraud - Wang, Ziwei (Journal of business ethics, 2024)
This study focuses on learning effects between firms connected by common ownership. We explore the learning effects in a certain setting that how decision-makers in focal firms learn from punishments for fraudulent disclosure in their co-owned firms. Baseline results show that punishments for fraudulent disclosure in co-owned firms reduce information disclosure fraud in focal firms. The effects still exist after excluding other potential channels of learning. In mechanism analyses, similarities between focal firms and their co-owned firms and influential common shareholders enhance the learning effects. Further, after the events in co-owned firms, there is improvement in internal control in focal firms, which contributes to the reduction of fraudulent disclosure. Additionally, empirical results mitigate the concern that the reduction of fraud is not driven by the learning argued in this paper but decision-makers alternatively conducting more other unethical behaviors such as real earnings management. In sum, empirical results support the existence of learning effects. As common ownership is an important but highly underexplored linkage between firms, future research can study learning effects between firms connected by common ownership in other suitable settings.